A cash transfer plus gender transformative economic empowerment intervention seeking to improve the wellbeing of caregivers of children and adolescents living with HIV in South Africa: a feasibility study protocol for a pilot cluster randomized trial - Darshini Govindasamy; Nwabisa Shai; Nelly Mwandacha; Stanley Carries; Nokwanda Sithole; Kalysha Closson; Arvin Bhana; Lovemore Sigwadhi; Laura Washington; Andrew Gibbs; Angela Kaida (Pilot and Feasibility Studies)
Abstract Background In sub-Saharan Africa, HIV care is dependent on informal caregiving, typically by female family members. Informal caregiving has been associated with numerous negative effects on caregivers (i.e., depression, intimate partner violence (IPV), financial insecurity). These factors impact caregivers’ ability to provide care and their own wellbeing. South Africa is home to approximately 17% of the world’s children and adolescents living with HIV (CALHIV), making the development of initiatives that mitigate the negative effects of caregiving critical. This protocol details the design of a cluster randomized trial seeking to assess the feasibility, preliminary effectiveness, cost-effectiveness, and acceptability of a cash transfer plus gender transformative economic empowerment intervention for improving psychological wellbeing, depressive symptoms, gender equality, and economic outcomes of caregivers of CALHIV. Methods Caregivers of CALHIV will be recruited from public sector HIV clinics within the eThekwini Municipality, KwaZulu-Natal, South Africa. Clusters will be randomly assigned to intervention or control groups. Participants in the intervention arm (n = 120) will receive cash transfers (ZAR350, USD $18.79) and enroll in a program (10 workshop sessions) over a 6-month period. Participants in the control arm (n = 120) will receive a monthly cash transfer (ZAR350, USD $18.79) for a 6-month period and a once-off standard mobile message, encouraging linkage to healthcare services. Participants will be interviewed at baseline and endline, at the 7-month mark, to collect socio-demographic, health and wellbeing status, IPV, costs and earnings, and food security data. The primary outcomes include consent rate, overall retention rate, workshops retention rate, cash transfer protocol adherence, staff perceptions on implementation, psychological wellbeing, depressive symptoms, and IPV. A qualitative study and economic evaluation will be conducted alongside the main trial to probe participant perceptions of the intervention and assess cost and cost-effectiveness. Discussion This trial has the potential to inform a larger confirmatory trial which will be valuable for informing post-pandemic recovery efforts for caregivers of CALHIV and others disproportionally burdened by compounding health and social crises. Trial registration PACTR202311618532061. Registry name: Pan African Clinical Trial Registry (PACTR), retrospectively registered on November 21, 2023; The first participant was enrolled on August 24, 2023.